Pembrolizumab Plus Chemotherapy in Metastatic Thymic Carcinoma: A Case Report - Thomas, Quentin Dominique; Basse, Clémence; Luporsi, Marie; Girard, Nicolas (Frontiers in Oncology, 2022)
Metastatic thymic carcinomas have a poor prognosis. Pembrolizumab, an anti-PD-1 antibody, has recently been evaluated for patients with metastatic thymic carcinomas progressing after at least one line of platinum-based chemotherapy. The antitumor activity of immunotherapy appears to be promising for these patients and pembrolizumab in monotherapy is actually a treatment option in second metastatic line. To the best of our knowledge, we report the first case of a patient treated for metastatic thymic adenocarcinoma with a combination of chemotherapy–immunotherapy. The patient is a 46-year-old man with metastatic thymic adenocarcinoma treated in third metastatic line with a combination of pembrolizumab plus platinum-based chemotherapy with a very good metabolic tumor response. He had a progression-free survival of 7.9 months and did not experience any severe side effects related to pembrolizumab. The association of immunotherapy and chemotherapy, as in non-small cell and small cell lung cancers, could be of interest for future therapeutic trials evaluating the survival of patients with metastatic thymic carcinoma.